Social relations in Ottoman Diyarbekir, 1870-1915 - Jongerden, Joost.; Verheij, Jelle. (The Ottoman Empire and its Heritage, 2012)
Social Relations in Ottoman Diyarbekir, 1870-1915 offers new, microhistoric and non-nationalist perspectives on the late 19th century history of the province of Diyarbekir. Focusing on a period dominated by violent conflicts between the authorities and various local elites and population groups of the region - urban Muslims, Kurds, Armenians, Syrian Christians and others - this book offers new insights into the social history of the region and the origins of the Armenian and Kurdish \'Questions\', which were to gain such prominence in the 20th century.